Summation inequality and its application to stability analysis for time‐delay systems. Issue 4 (1st February 2016) - Chen, Jun; Lu, Junwei; Xu, Shengyuan
Abstract : This study proposes a new summation inequality, called the free‐matrix‐based summation inequality, which further extends certain existing summation inequalities in the literature. Less conservative stability criteria are proposed for discrete‐time systems with time‐varying delays. Numerical examples are provided to demonstrate the improvement of the proposed approach.